Developing clinical practice guidelines for epilepsy: A report from the ILAE Epilepsy Guidelines Working Group. (30th October 2015) - Sauro, Khara M.; Wiebe, Samuel; Perucca, Emilio; French, Jacqueline; Dunkley, Colin; de Marinis, Alejandro; Kirkpatrick, Martin; Jetté, Nathalie
Summary: Clinical practice guidelines (CPGs) contain evidence‐based recommendations to guide clinical care, policy development, and quality of care improvement. A recent systematic review of epilepsy guidelines identified considerable variability in the quality of available guidelines. Although excellent frameworks for CPG development exist, processes are not followed uniformly internationally, and resources to develop CPGs may be limited in certain settings. An International League Against Epilepsy (ILAE) working group was charged with proposing methodology to guide the development of future epilepsy‐specific CPGs. A comprehensive literature search (1985–2014) identified articles related to CPG development and handbooks. Guideline handbooks were included if they were publicly available, and if their methodology had been used to develop CPGs. The working group's expertise also informed the creation of methodologies and processes to develop future CPGs for the ILAE. Five handbooks from North America (American Academy of Neurology), Europe (Scottish Intercollegiate Guidelines Network & National Institute for Health and Care Excellence), Australia (National Health and Medical Research Council), World Health Organization (WHO), and additional references were identified to produce evidence‐based, consensus‐driven methodology for development of epilepsy‐specific CPGs. Key components of CPG development include the following: identifying the topic and defining the scope; establishing a working group; identifying and evaluating the evidence; formulating recommendations and determining strength of recommendations; obtaining peer reviews; dissemination, implementation, and auditing; and updating and retiring the CPG. A practical handbook and toolkit was developed. The resulting CPG development toolkit should facilitate the development of high‐quality ILAE CPGs to improve the care of persons with epilepsy.